(Î±,Î²,Î´)- Neighborhood for Certain Analytic Functions with Negative Coefficients (European Journal of Pure and Applied Mathematics, 2011)
In this paper, we introduce (Î±,Î²,Î´)- neighborhoods of analytic functions with negative coefficients. Furthermore, we obtain some interesting results for functions belonging to this neighborhoods.